Contribution of Leadership Style, Competence, and Motivation to Employee Performance in the Badan Keuangan and Aset Daerah Kota Kupang - Juhaini Alie; Jefirstson Richset Riwukore; Godlyfe Smarthene Ryck Hawai (Enrichment : Journal of Management, 2022)
The purpose of this research is to analyze and prove the influence of leadership style, competence, and motivation on employee performance. This research was conducted for 5 months (January-May 2022) at the Office of the Badan Keuangan dan Aset Daerah Kota Kupang. This research is classified as quantitative research using a method of survey confirmative verification (associative). The research population was 103 employees whose sample was determined based on the census technique (saturated sample) so the sample was 103 respondents. The type of research data consists of primary data and secondary data. Techniques to obtain data using questionnaires (Likert scale), interviews, and documentation. Data analysis used multiple linear regression analysis (partial test and simultaneous test). The results showed that leadership style, competence, and motivation positively and significantly affected performance either partially or simultaneously. This is because the entire t-count value obtained by each variable is greater than the t-table and also the F-count is greater than the F-table with a significance value of < α 0.05. The contribution of leadership style to performance is 60.2%, competence to performance is 52.9%, and motivation to performance is 43.7%. In general, the contribution of leadership style, competence, and motivation variables to performance is 68.1%.